Decreased Pulmonary Function Measured in Children Exposed to High Environmental Relative Moldiness Index Homes - Vesper, Stephen J. (Bentham Open, 2013)
BACKGROUND: Exposures to water-damaged homes/buildings has been linked to deficits in respiratory health. However, accurately quantifying this linkage has been difficult because of the methods used to assess water damage and respiratory health. PURPOSE: The goal of this analysis was to determine the correlation between the water-damage, as defined by the Environmental Relative Moldiness Index (ERMI) value in an asthmatic child’s home, and the child’s pulmonary function measured by spirometry, “forced expiratory volume in one second, percent predicted” or FEV1%. METHODS: This analysis utilized data obtained from the “Heads-off Environmental Asthma in Louisiana” (HEAL) study. The children (n= 109), 6 to 12 years of age, who had completed at least one spirometry evaluation and a dust sample collected for ERMI analysis from the home at approximately the same time as the spirometry testing, were included in the analysis. Statistical evaluation of the correlation between ERMI values and FEV1% was performed using the Spearman’s Rank Correlation analysis. The relationship between ERMI values and FEV1% was performed using B-spline regression. RESULTS: The average ERMI value in the HEAL study homes was 7.3. For homes with ERMI values between 2.5 and 15, there was a significant inverse correlation with the child’s lung function or FEV1% measurement (Spearman’s rho -0.23; p= 0.03), i.e. as the ERMI value increased, the FEV1% value decreased. CONCLUSIONS: Measures of water-damage (the ERMI) and clinical assessments of lung function (FEV1%) provided a quantitative assessment of the impact of water-damaged home exposures on children’s respiratory health.